Bilateral Complete Oculomotor Palsy in Tubercular Meningitis - Gaba, Saurabh (Cureus, 2020)
A 20-year-old female presented to the emergency department with fever, anorexia, headache, and neck stiffness for two weeks with recent onset of diplopia and ptosis. She was found to have bilateral symmetrical and complete oculomotor palsy. The diagnosis of tubercular meningitis (TBM) was established on magnetic resonance imaging of the brain and cerebrospinal fluid examination. The oculomotor palsy was attributed to tubercular exudates along the ventral surface of midbrain. Although cranial nerves palsies are common in TBM, such a pattern is rarely seen and has been reported only in the context of tuberculoma in midbrain. She was treated with anti-tubercular therapy for nine months, but there was only partial recovery of the oculomotor function.